DEVELOPING THEORETICAL CONCEPTS THROUGH EPIC WORKS ANALYSIS - Marasulova , Umida Shahrisabz (Educational Research in Universal Sciences, 2023)
The article forms the necessary theoretical ideas and skills as a result of the use of advanced teaching methods and methods leading to a research and creative approach in the organization of literary studies. The level of effectiveness of the lesson is determined by the knowledge, creativity of the teacher, the ability to scientifically and methodically organize the lesson. After all, only the work of a teacher who can awaken in the student a love for the world of art, a sense of admiration for samples of artistic creativity, will be performed effectively.